Differential Expression of PD-L1 in Central and Peripheral and TTF1-Positive and -Negative Small-Cell Lung Cancer - Yu, Shili; Jia, Meng; Li, Yuemin; Sun, Ping-Li; Gao, Hongwen (Frontiers in Medicine, 2021)
Background：Central and peripheral location as well as thyroid transcription factor-I (TTF-1) expression was reported to be associated with different characteristics and prognosis of small-cell lung cancer (SCLC). This study aimed to investigate differential expression of PD-L1 in different SCLC subtypes, and in biopsy and resection specimens. Methods: We retrospectively analyzed 142 SCLC tumor samples using immunohistochemistry to correlate PD-L1 (22C3) expression with clinicopathologic features and survival data. Results: PD-L1 expression was found in 19.7% SCLCs (28/142) and was more frequent in females than in males (32%, 16/50 vs. 13%, 12/92, p = 0.009), in central type than in peripheral type SCLCs (26%, 26/100 vs. 4.8%, 2/42, p = 0.003), and in TTF-1 positive than in negative SCLCs (23.8%, 25/105 vs. 8.1%, 3/37, p = 0.039). PD-L1 expression was associated with vascular (p = 0.001) and lymphatic invasion (p = 0.001). There was no significant difference in PD-L1 expression between biopsy and resection specimens. On univariate analysis, patients with PD-L1 expression had significantly shorter progression-free survival (PFS; p = 0.026) and overall survival (OS; p = 0.012). Multivariate analysis revealed that PD-L1 expression was an independent prognostic factor for OS (HR, 2.317; 95% CI 1.199–4.478; p = 0.012) and PFS (HR, 1.636; 95% CI 0.990–2.703; p = 0.051) in SCLC. Conclusions: PD-L1 expression was more frequent in central type, TTF-1 positive SCLCs, and predicted a poor clinical outcome in these patients. Therefore, tumor location and TTF-1 expression could predict expression status of PD-L1, and could potentially serve as clinical response to immunotherapy.